MOLECULAR MECHANISMS DEFINING APPLICATION OF GLYCINE AND ZINC COMBINATIONIN CORRECTION OF STRESS AND ANXIETY MAIN MANIFESTATIONS - V. N. Shishkova; Y. R. Nartsissov; V. Y. Titova; E. V. Sheshegova (Фармация и фармакология (Пятигорск))
The aim of the work was to carry out a systematic analysis of the molecular mechanisms that determine the possibility of a combined use of amino acid glycine and zinc compounds for the treatment of patients with manifestations of stress and anxiety.Materials and methods. Information retrieval (Scopus, PubMed) and library (eLibrary) databases were used as research tools. In some cases, the ResearchGate application was applied for a semantic search. The analysis and generalization of references was carried out on the research topic, covering the period from 2000 to the present time.Results. It has been shown that amino acid glycine, along with gamma-aminobutyric acid (GABA), is a key neurotransmitter that regulates physiological inhibition processes in the central nervous system (CNS) by increasing transmembrane conductance in specific pentameric ligand-gated ion channels. The introduction of zinc ions can potentiate the opening of these receptors by increasing their affinity for glycine, resulting in an inhibitory processes increase in CNS neurons. The replenishment of the glycine and zinc combined deficiency is an important element in the correction of a post-stress dysfunction of the central nervous system. A balanced intake of zinc and glycine is essential for most people who experience daily effects of multiple stresses and anxiety. This combination is especially useful for the people experiencing a state of chronic psycho-emotional stress and maladaptation, including those who have a difficulty in falling asleep.Conclusion. A balanced maintenance of the zinc and glycine concentration in the body of a healthy person leads to the development of a stable anti-anxiety effect, which is accompanied by the normalization of the sleep-wake rhythm, which makes it possible to have a good rest without any loss of working efficiency after waking up.